Elevated-temperature strength and wear behavior of Al80Mn11Ce9 processed by laser powder bed fusion - Katharina Gabrysiak; Anne Veronika Boehm; Tobias Gustmann; Christoph Leyens; Uta Kühn (Journal of Materials Research and Technology, 2025)
Many components in the mobility sector are subjected to elevated temperatures and tribological demands while requiring light weight construction at the same time. Laser powder bed fusion (PBF-LB) enables the formation of unique microstructures through process-related high cooling rates, resulting in desirable component properties. In this study, an Al80Mn11Ce9 (wt.%) alloy was fabricated by PBF-LB, achieving a microstructure consisting of a supersaturated Al-matrix and fine-sized, metastable, high-strength Al20Mn2Ce particles. The mechanical performance and wear rate of this alloy were benchmarked against the industrially employed, heat-treated Al-7075 alloy. Both alloys reach high hardness and compressive strength, while Al80Mn11Ce9 outperforms the reference material in terms of wear resistance and strength retention at 300 °C. Under dry sliding against steel, Al80Mn11Ce9 forms an iron-oxide-rich, protective, mechanically mixed layer across all tested conditions, including loads up to 30 N and sliding times up to 5 h. The primary limitation of this alloy is the ductility-limited strength at room temperature. Nevertheless, this study estimates the potential of Al80Mn11Ce9 for lightweight applications requiring durability at elevated temperatures and high tribological performance.